Coating slurry and preparation method thereof, pole piece and battery
By using a combination of composite conductive agent and modified binder in lithium-ion batteries, the mass ratio and particle size are optimized, and combined with acid-base regulators, the problem of insufficient adhesion of carbonated aluminum foil in lithium-ion batteries is solved, and the problem of insufficient adhesion in lithium-ion batteries is improved. The electrical and thermal conductivity of the battery extends battery life and improves consistency.
Patent Information
- Application Number
- CN202411282387.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-24
AI Technical Summary
In existing lithium-ion batteries, carbonated aluminum foil has shortcomings in improving the adhesion between active substances and current collectors, resulting in high internal resistance and serious polarization of the battery, affecting battery life and consistency.
Using a coating slurry, including composite conductive agents, modified binders and acid-base regulators, the mass ratio and particle size are optimized to improve conductivity by combining conductive carbon black, modified conductive graphite and conductive polymer. and thermal conductivity, and pH is adjusted by acid-base regulators to enhance adhesion.
The conductive and thermal conductivity of the coating slurry is significantly improved, the adhesion to the substrate is enhanced, the internal resistance of the battery is reduced, the battery life is extended and the consistency is improved.
Smart Images

Figure BDA0005042061600000141 
Figure BDA0005042061600000151 
Figure BDA0005042061600000152
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a coating slurry and a preparation method thereof, a pole piece, and a battery. Background Art
[0002] With the advancement of lithium-ion battery technology, the positive current collector of lithium-ion batteries includes but is not limited to ordinary aluminum foil. Carbon-coated aluminum foil has also been gradually used in recent years. Especially in lithium iron phosphate batteries, carbon-coated aluminum foil can effectively improve the adhesion between active materials and current collectors, reduce battery internal resistance, reduce polarization, and improve battery life and consistency. How to obtain carbon-coated aluminum foil with excellent performance has become a research hotspot in recent years. Summary of the invention
[0003] Purpose of the invention: The embodiment of the present application provides a coating slurry having excellent electrical and thermal conductivity.
[0004] The first aspect of the present application provides a coating slurry, including a composite conductive agent;
[0005] The composite conductive agent comprises conductive carbon black, modified conductive graphite and conductive polymer; the modified conductive graphite has unsaturated carbon-carbon double bonds and siloxane groups.
[0006] In some embodiments, the coating slurry also includes a modified binder and a first acid-base regulator, the modified binder having an unsaturated carbon-carbon double bond; the mass ratio of the composite conductive agent to the modified binder is 42-61:40-55; the mass ratio of the modified binder to the first acid-base regulator is 40-55:3-8.
[0007] In some embodiments, the mass ratio of the conductive carbon black, the modified conductive graphite, and the conductive polymer is 20-28:18-25:4-8.
[0008] In some embodiments, the particle size D50 of the modified conductive graphite is 3 um to 8 um.
[0009] In some embodiments, the conductive polymer is selected from PEDOT:PSS.
[0010] In some embodiments, the pH value of the coating slurry is 4-6.
[0011] In some embodiments, the solid content of the coating slurry is 8% to 18%.
[0012] A second aspect of the present application provides a method for preparing a coating slurry, comprising:
[0013] Dissolving the composite conductive agent, the modified binder, the first acid-base regulator and the wetting agent in deionized water, stirring and mixing, to obtain a coating slurry;
[0014] The composite conductive agent comprises conductive carbon black, modified conductive graphite and conductive polymer; the modified conductive graphite has unsaturated carbon-carbon double bonds and siloxane groups.
[0015] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the conductive carbon black is a1, the mass proportion of the modified conductive graphite is a2, and the mass proportion of the conductive polymer is a3, satisfying: 0.11≤a3 / (a1+a2)≤0.18.
[0016] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the composite conductive agent is A, the mass proportion of the modified binder is B, and the following condition is satisfied: 0.81≤A / B≤1.50.
[0017] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the modified binder is B, the mass proportion of the first acid-base regulator is C, and the following condition is satisfied: 0.12≤C / B≤0.32.
[0018] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the conductive carbon black is 20% to 30%.
[0019] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the modified conductive graphite is 18% to 25%.
[0020] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the conductive polymer is 4% to 8%.
[0021] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass of the modified binder accounts for 40% to 55%.
[0022] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the first acid-base regulator is 3% to 8%.
[0023] In some embodiments, based on the total mass of the deionized water, the mass proportion of the wetting agent is 1% to 2%.
[0024] In some embodiments, the method for preparing the modified conductive graphite comprises:
[0025] After the conductive graphite and the first solvent are mixed, the first silane coupling agent and the polyether-modified siloxane are added, and the mixture is stirred, mixed and reacted to obtain the modified conductive graphite;
[0026] The molar ratio of the conductive graphite, the first silane coupling agent and the polyether-modified siloxane is 1:0.05:0.05;
[0027] The first silane coupling agent is selected from silane coupling agents containing unsaturated carbon-carbon double bonds at the ends;
[0028] The first solvent is selected from at least one of toluene, dimethyl ketone and xylene.
[0029] In some embodiments, the method for preparing the modified binder comprises:
[0030] Under an inert atmosphere, dissolving a crosslinking agent and a second silane coupling agent in deionized water, heating, stirring, reacting, and then adding a second acid-base regulator and keeping the temperature to obtain the modified binder;
[0031] The molar ratio of the cross-linking agent, the first silane coupling agent and the second acid-base adjusting agent is 0.05:1:1;
[0032] The cross-linking agent is selected from at least one of acrylic acid, acrylic ester, acrylonitrile, and acrylic acid-hydroxylactone;
[0033] The second silane coupling agent is selected from silane coupling agents containing unsaturated carbon-carbon double bonds at the ends;
[0034] The second acid-base regulator is selected from at least one of ammonium bicarbonate, sodium hydroxide, lithium hydroxide, and calcium hydroxide.
[0035] The third aspect of the present application provides a pole piece, including a current collector, the current collector including a substrate and a coating located on at least one side of the substrate, the coating being prepared using the coating slurry as described above, or being prepared using a coating slurry prepared using the coating slurry preparation method as described above.
[0036] A fourth aspect of the present application provides a battery, comprising the pole piece as described above.
[0037] The present application provides a coating slurry, including a composite conductive agent; wherein the composite conductive agent includes conductive carbon black, modified conductive graphite and conductive polymer; the modified conductive graphite has unsaturated carbon-carbon double bonds and siloxane groups. Conductive carbon black is a granular material, which mainly provides short-range connection and conductivity; the conductive polymer has good electrical and thermal conductivity, and the conductive graphite is a flaky material, which mainly provides surface connection and conductivity, and the modified conductive graphite is grafted with unsaturated carbon-carbon double bonds, so that the modified conductive graphite has better compatibility with the binder and is easier to disperse, and the modified conductive graphite is grafted with siloxane groups, which has a good effect on improving the fluidity and leveling of the coating slurry, so that the coating slurry can be more evenly coated on the surface of the substrate. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0039] In the present specification, a numerical range expressed using "to" means a range including the numerical values described before and after "to" as the minimum value and the maximum value, respectively.
[0040] The first aspect of the present application provides a coating slurry, and the present application will be described in detail below in conjunction with specific embodiments.
[0041] A coating slurry comprises a composite conductive agent; wherein the composite conductive agent comprises conductive carbon black, modified conductive graphite and conductive polymer; the modified conductive graphite has unsaturated carbon-carbon double bonds and siloxane groups.
[0042] It can be understood that conductive carbon black is a granular material, which mainly provides short-range connection and conduction; conductive polymers have good electrical and thermal conductivity, and modified conductive graphite is a flaky material, which mainly provides surface connection and conduction, and the modified conductive graphite is grafted with unsaturated carbon-carbon double bonds, which makes the modified conductive graphite more compatible with the binder and easier to disperse, and the modified conductive graphite is grafted with siloxane groups, which has a good effect on improving the fluidity and leveling of the coating slurry, so that the coating slurry can be more evenly coated on the substrate surface.
[0043] In some embodiments, the coating slurry further comprises a modified binder and a first acid-base regulator, wherein the modified binder has an unsaturated carbon-carbon double bond; the mass ratio of the composite conductive agent to the modified binder is 42-61:40-55; the mass ratio of the modified binder to the first acid-base regulator is 40-55:3-8. Specifically, the mass ratio of the composite conductive agent to the modified binder can be any one of 42:40, 42:55, 45:45, 50:50, 55:55, 61:40, 61:55, or any two ratios; the mass ratio of the modified binder to the first acid-base regulator can be any one of 40:3, 40:8, 45:5, 50:8, 55:3, or 55:8, or any two ratios.
[0044] It can be understood that the modified binder has an unsaturated carbon-carbon double bond, which can react with the unsaturated carbon-carbon double bond in the modified conductive graphite, so that the modified conductive graphite and the modified binder are more compatible and easier to disperse. The present application controls the mass ratio of the composite conductive agent and the modified binder to be 42-61:40-55, and ensures the adhesion between the coating slurry and the substrate under the premise that the coating slurry has good thermal and electrical conductivity; in addition, the adhesion between the coating slurry and the substrate is related to the mass proportion of the binder in the coating slurry. It is also related to the pH value of the coating slurry. When the pH value increases to a certain range, the adhesion between the coating slurry and the substrate will also increase accordingly. The modified binder is an acidic material. If no acid-base regulator is added, the pH value of the coating slurry is low and the adhesion between the coating and the substrate will be reduced. The present application adds a first acid-base regulator to the coating slurry and controls the mass ratio of the modified binder to the first acid-base regulator to be 40-55:3-8, thereby adjusting the pH value of the coating slurry and improving the adhesion between the coating slurry and the substrate.
[0045] In some embodiments, the first acid-base regulator is selected from at least one of sodium hydroxide, lithium hydroxide, ammonium bicarbonate, and calcium hydroxide.
[0046] In some embodiments, the mass ratio of the conductive carbon black, the modified conductive graphite and the conductive polymer is 20 to 28:18 to 25:4 to 8. Specifically, the mass ratio of the conductive carbon black, the modified conductive graphite and the conductive polymer can be any one of 20:18:4, 20:25:8, 28:25:8, 28:18:4, 23:20:5, 25:22:6 or any two of the ratios.
[0047] It can be understood that conductive carbon black is a granular material that mainly provides short-range connection and conduction; conductive polymers have good electrical and thermal conductivity; modified conductive graphite is a flaky material that mainly provides surface connection and conduction. The present application improves the electrical conductivity and thermal conductivity of the coating slurry by controlling the mass ratio of conductive carbon black, modified conductive graphite and conductive polymer to 20-28:18-25:4-8, thereby improving the electrical conductivity and thermal conductivity of the current collector.
[0048] In some embodiments, the conductive carbon black is selected from at least one of carbon black, acetylene black, and Ketjen black.
[0049] In some embodiments, the particle size D50 of the modified conductive graphite is 3 um to 8 um. Specifically, the particle size D50 of the modified conductive graphite can be any one of 3 um, 4 um, 5 um, 6 um, 7 um, and 8 um, or a range consisting of any ratio.
[0050] It can be understood that the particle size D50 of the modified conductive graphite is 3 um to 8 um, which makes the modified conductive graphite easy to disperse and not easy to agglomerate.
[0051] In some embodiments, the conductive polymer is selected from PEDOT:PSS.
[0052] It can be understood that the conductive polymer PEDOT:PSS has good electrical and thermal conductivity.
[0053] In some embodiments, the pH value of the coating slurry is 4 to 6. Specifically, the pH value of the coating slurry can be any one of 4, 4.5, 5, 5.5, 6 or a range consisting of any ratio.
[0054] It is understood that by adjusting the pH value of the coating slurry to 4-6, the bonding force between the coating slurry and the substrate can be improved.
[0055] In some embodiments, the solid content of the coating slurry is 8% to 18%. Specifically, the solid content of the coating slurry can be any one of 8%, 10%, 12%, 14%, 16%, 18% or any ratio thereof.
[0056] It can be understood that by making the solid content of the coating slurry be 8% to 18%, it is beneficial to the coating and film formation of the coating slurry.
[0057] A second aspect of the present application provides a method for preparing a coating slurry, comprising:
[0058] Dissolving the composite conductive agent, the modified binder, the first acid-base regulator and the wetting agent in deionized water, stirring and mixing, to obtain a coating slurry;
[0059] The composite conductive agent includes conductive carbon black, modified conductive graphite and conductive polymer; the modified conductive graphite has unsaturated carbon-carbon double bonds and siloxane groups.
[0060] It can be understood that conductive carbon black is a granular material, which mainly provides short-range connection and conduction; conductive polymers have good electrical and thermal conductivity, and modified conductive graphite is a flaky material, which mainly provides surface connection and conduction, and the modified conductive graphite is grafted with unsaturated carbon-carbon double bonds, which makes the modified conductive graphite more compatible with the binder and easier to disperse, and the modified conductive graphite is grafted with siloxane groups, which has a good effect on improving the fluidity and leveling of the coating slurry, so that the coating slurry can be more evenly coated on the substrate surface.
[0061] In some embodiments, a method for preparing a coating slurry comprises:
[0062] Adding the modified binder and deionized water into the mixer to perform the first stirring and mixing;
[0063] Then, conductive carbon black and modified conductive graphite are added into the stirrer and stirred and mixed for the second time;
[0064] Then, the conductive polymer is added to the stirrer and stirred and mixed for a third time;
[0065] Then, the first acid-base regulator is added to the stirrer, and the mixture is stirred for the fourth time;
[0066] Then, a wetting agent is added to the stirrer and stirred and mixed for the fifth time to obtain a coating slurry.
[0067] In some embodiments, after obtaining the coating slurry, the method further includes sanding the coating slurry.
[0068] It can be understood that by sanding the coating slurry, the particle size of the slurry can be reduced, which is beneficial for coating the slurry into a coating.
[0069] In some embodiments, the first stirring time is 30 min to 60 min. Specifically, the first stirring time can be any one of 30 min, 40 min, 50 min, and 60 min, or a range consisting of any two of the ratios.
[0070] In some embodiments, the second stirring time is 60 min to 120 min. Specifically, the first stirring time can be any one of 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, and 120 min, or a range consisting of any two of the ratios.
[0071] In some embodiments, the third stirring time is 30 min to 60 min. Specifically, the third stirring time can be any one of 30 min, 40 min, 50 min, and 60 min, or a range consisting of any two of the ratios.
[0072] In some embodiments, the fourth stirring time is 30 min to 60 min. Specifically, the fourth stirring time can be any one of 30 min, 40 min, 50 min, and 60 min, or a range consisting of any two of the ratios.
[0073] In some embodiments, the fifth stirring time is 30 min to 60 min. Specifically, the fifth stirring time can be any one of 30 min, 40 min, 50 min, and 60 min, or a range consisting of any two of the ratios.
[0074] In some embodiments, the first acid-base regulator is selected from at least one of sodium hydroxide, lithium hydroxide, ammonium bicarbonate, and calcium hydroxide.
[0075] In some embodiments, the wetting agent is selected from at least one of isopropyl alcohol and ethanol.
[0076] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the conductive carbon black is a1, the mass proportion of the modified conductive graphite is a2, and the mass proportion of the conductive polymer is a3, satisfying: 0.11≤a3 / (a1+a2)≤0.18. Specifically, the ratio of a3 / (a1+a2) can be any one of 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18 or a range consisting of any two ratios.
[0077] It can be understood that conductive carbon black is a granular material, which mainly provides short-range connection and conduction; conductive polymer has good electrical and thermal conductivity, and modified conductive graphite is a flaky material, which mainly provides surface connection and conduction. By making the mass proportion of conductive carbon black a1, the mass proportion of modified conductive graphite a2, and the mass proportion of conductive polymer a3 satisfy: 0.11≤a3 / (a1+a2)≤0.18, the electrical conductivity and thermal conductivity of the coating slurry can be improved, thereby improving the electrical conductivity and thermal conductivity of the current collector.
[0078] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the composite conductive agent is A, the mass proportion of the modified binder is B, and the following conditions are satisfied: 0.81≤A / B≤1.50. Specifically, the ratio of A / B can be any one of 0.81, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, or a range consisting of any two ratios.
[0079] It can be understood that the conductive properties of the coating slurry are related to the mass proportion of the composite conductive agent in the coating slurry, and the adhesion between the coating slurry and the substrate is related to the mass proportion of the modified binder in the coating slurry. The present application satisfies the following conditions: 0.81≤A / B≤1.50 by making the mass proportion A of the composite conductive agent and the mass proportion B of the modified binder satisfy: 0.81≤A / B≤1.50. On the premise that the coating slurry has good conductive properties, the adhesion between the coating slurry and the substrate is ensured, that is, the peeling force of the current collector is ensured, thereby improving the peeling force between the current collector and the electrode coating, and improving the rate performance and cycle performance of the battery.
[0080] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the modified binder is B, the mass proportion of the first acid-base regulator is C, and the following is satisfied: 0.12≤C / B≤0.32. Specifically, the ratio of C / B can be any one of 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.32 or a range consisting of any two ratios.
[0081] It can be understood that the modified binder is an acidic material. If no acid-base regulator is added, the pH value of the coating slurry will be low and the adhesion between the coating and the substrate will be reduced. The present application satisfies the following conditions: 0.12≤C / B≤0.32 by making the mass proportion of the modified binder B and the mass proportion of the first acid-base regulator C. Under the premise of ensuring the adhesion of the coating slurry, the pH value of the coating slurry can be improved, thereby enhancing the adhesion between the coating and the substrate.
[0082] In some embodiments, the mass proportion of the conductive carbon black is 20% to 30% based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator. Specifically, the mass proportion of the conductive carbon black is any one of 20%, 22%, 24%, 26%, 28% and 30% based on the total mass of the coating slurry, or a range consisting of any two values.
[0083] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the modified conductive graphite is 18% to 25%. Specifically, based on the total mass of the coating slurry, the mass proportion of the modified conductive graphite can be any one of 18%, 20%, 23%, 25%, or any two of the values.
[0084] In some embodiments, the weight percentage of the conductive polymer is 4% to 8% based on the total weight of the composite conductive agent, the modified binder and the first acid-base regulator. Specifically, the weight percentage of the conductive polymer can be any one of 4%, 5%, 6%, 7%, and 8% or a range consisting of any two values based on the total weight of the coating slurry.
[0085] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the modified binder is 40% to 55%. Specifically, based on the total mass of the coating slurry, the mass proportion of the modified binder can be any one of 40%, 45%, 50%, 55%, or a range consisting of any two values.
[0086] In some embodiments, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the first acid-base regulator is 3% to 8%. Specifically, based on the total mass of the coating slurry, the mass proportion of the first acid-base regulator can be any one of 3%, 4%, 5%, 6%, 7%, 8%, or a range consisting of any two values.
[0087] In some specific embodiments, the mass proportion of the wetting agent is 1% to 2% based on the total mass of the deionized water. Specifically, the mass proportion of the wetting agent can be any one of 1%, 1.2%, 1.5%, 1.7%, and 2%, or a range consisting of any two values, based on the total mass of the deionized water.
[0088] In some embodiments, a method for preparing modified conductive graphite comprises:
[0089] After the conductive graphite and the first solvent are mixed, the first silane coupling agent and the polyether modified siloxane are added, stirred, mixed and reacted to obtain the modified conductive graphite.
[0090] In some embodiments, the molar ratio of the conductive graphite, the first silane coupling agent, and the polyether-modified siloxane is 1:0.05:0.05.
[0091] In some embodiments, the first silane coupling agent is selected from silane coupling agents containing an unsaturated carbon-carbon double bond at the terminal.
[0092] In some embodiments, the first silane coupling agent is selected from at least one of vinyl trimethoxy silane, acryl triethoxy silane, vinyl tri (2-methoxyethoxy) silane, and acryl trimethoxy silane.
[0093] In some embodiments, the first solvent is selected from at least one of toluene, dimethyl ketone, and xylene.
[0094] In some embodiments, the reaction time is 4 to 5 hours. Specifically, the reaction time is any one of 4 hours, 4.5 hours, and 5 hours, or a range consisting of any two of the values.
[0095] In some embodiments, a method for preparing a modified binder comprises:
[0096] Under an inert atmosphere, the crosslinking agent and the second silane coupling agent are dissolved in deionized water, heated, stirred, reacted, and then the second acid-base regulator is added and kept warm to obtain a modified adhesive.
[0097] In some embodiments, the molar ratio of the crosslinking agent, the first silane coupling agent, and the second acid-base modifier is 0.05:1:1;
[0098] In some embodiments, the crosslinking agent is selected from at least one of acrylic acid, acrylic acid ester, acrylonitrile, and acrylic acid-acrylic acid hydroxylactone;
[0099] In some embodiments, the second silane coupling agent is selected from silane coupling agents containing an unsaturated carbon-carbon double bond at the terminal.
[0100] In some specific embodiments, the second silane coupling agent is selected from at least one of vinyl trimethoxy silane, acryl triethoxy silane, vinyl tri (2-methoxyethoxy) silane, and acryl trimethoxy silane.
[0101] In some embodiments, the second acid-base regulator is selected from at least one of ammonium bicarbonate, sodium hydroxide, and lithium hydroxide.
[0102] In some embodiments, the inert atmosphere is selected from nitrogen.
[0103] In some embodiments, the reaction temperature is 60° C. to 80° C. Specifically, the reaction temperature can be any one of 60° C., 65° C., 70° C., 75° C., and 80° C., or a range consisting of any two of the values.
[0104] In some embodiments, the insulation time is 45 min to 90 min. Specifically, the insulation time can be any one of 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, and 90 min, or a range consisting of any two values.
[0105] In some embodiments, the present application also provides a current collector, including a substrate and a coating located on at least one side of the substrate, the coating is prepared using the coating slurry as described above, or is prepared using a coating slurry prepared using the coating slurry preparation method as described above.
[0106] In some embodiments, the present application also provides a method for preparing a current collector, comprising:
[0107] The coating slurry is coated on at least one side of the substrate and dried to obtain a current collector.
[0108] In some embodiments, the substrate is selected from any one of aluminum foil and composite aluminum foil.
[0109] In some embodiments, the drying temperature is 70°C to 105°C, and the drying time is 1 min to 4 min. Specifically, the drying temperature can be any one of 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, and 105°C, or a range consisting of any two values; the drying time can be any one of 1 min, 2 min, 3 min, and 4 min, or a range consisting of any two values.
[0110] In some embodiments, the coating method is selected from any one of gravure transfer coating and micro gravure transfer coating.
[0111] The third aspect of the present application also provides an electrode, which includes a current collector, and the current collector includes a substrate and a coating located on at least one side of the substrate, and the coating is prepared using the coating slurry as described above, or is prepared using a coating slurry prepared by the coating slurry preparation method as described above.
[0112] In some embodiments, the thickness of the coating layer is 0.5 μm to 2 μm. Specifically, the thickness of the coating layer can be any one of 0.5 μm, 1 μm, 1.5 μm, and 2 μm, or a range consisting of any two of the values.
[0113] The fourth aspect of the present application also provides a battery, comprising the pole piece as described above.
[0114] The following describes the invention in conjunction with specific embodiments.
[0115] Example 1
[0116] Modified conductive graphite:
[0117] The molar ratio of conductive graphite, propylene triethoxysilane, and polyether modified siloxane is 1:0.05:0.05;
[0118] Conductive graphite was dissolved in toluene, stirred for 30 minutes, and then propylene triethoxysilane and polyether modified siloxane were added, stirred and reacted for 4 hours to obtain modified conductive graphite.
[0119] Modified adhesive:
[0120] The molar ratio of acryltriethoxysilane, acrylic acid, and ammonium bicarbonate is 0.05:1:1;
[0121] Under a nitrogen atmosphere, acrylic acid and deionized water were mixed and stirred for 15 minutes, then the temperature was raised to 60°C, and propenyltriethoxysilane was added. The stirring and reaction were continued for 10 minutes. Ammonium bicarbonate was added, stirred for 10 minutes, and the mixture was kept warm for 60 minutes to obtain a modified adhesive.
[0122] Coating slurry:
[0123] Based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of conductive carbon black is a1, which is 20.1%; the mass proportion of modified conductive graphite is a2, which is 22.3%; the mass proportion of conductive polymer is a3, which is 4.8%; the composite conductive agent includes conductive carbon black, modified conductive graphite and conductive polymer, and the mass proportion of composite conductive agent is A, which is 47.2%; the mass proportion of modified binder is B, which is 47.1%; the mass proportion of the first acid-base regulator is C, which is 5.7%;
[0124] Add 0.45 kg of modified binder and 1.35 kg of deionized water into a double planetary mixer and stir for 40 min;
[0125] Then add 0.190 kg of conductive carbon black and 0.211 kg of modified conductive graphite into the double planetary mixer and stir for 60 min;
[0126] Then add 0.046 kg PEDOT:PSS into the double planetary mixer and stir for 120 min;
[0127] Then add 4.83 kg of deionized water and 0.054 kg of lithium hydroxide into the double planetary mixer and stir for 30 minutes;
[0128] Then, 0.06 kg of isopropanol was added into the double planetary mixer and stirred for 30 minutes to obtain a coating slurry. The solid content of the coating slurry was 13.3%.
[0129] Current collector:
[0130] The prepared coating slurry was sand-polished and then coated on both sides of the aluminum foil by gravure transfer coating. The coating thickness on one side was 1 μm. The coating was baked at 90° C. for 3 minutes to obtain a current collector.
[0131] Embodiments 2 to 8
[0132] The preparation methods of Examples 2 to 8 are the same as those of Example 1, except that: based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the conductive carbon black is adjusted to a1; the mass proportion of the modified conductive graphite is adjusted to a2; the mass proportion of the conductive polymer is adjusted to a3; the mass proportion of the composite conductive agent is adjusted to A; the mass proportion of the modified binder is adjusted to B; the mass proportion of the first acid-base regulator is adjusted to C.
[0133] Comparative Example 1
[0134] Add 0.45 kg of polyacrylic acid binder and 1.35 kg of deionized water into the double planetary mixer and stir for 40 minutes;
[0135] Then add 0.2250kg of conductive carbon black and 0.225kg of conductive graphite into the double planetary mixer and stir for 60min;
[0136] Add 3.75 kg of deionized water to the double planetary mixer and stir for 30 minutes;
[0137] Add 0.06 kg of isopropanol to the double planetary mixer and stir for 30 minutes;
[0138] After sand grinding, a coating slurry was obtained, and the solid content of the coating slurry was 13.6%.
[0139] Comparative Examples 2 to 4
[0140] The preparation methods of Comparative Examples 2 to 4 are the same as those of Example 1, except that: based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the conductive carbon black is adjusted to a1; the mass proportion of the modified conductive graphite is adjusted to a2; the mass proportion of the conductive polymer is adjusted to a3; the mass proportion of the composite conductive agent is adjusted to A; the mass proportion of the modified binder is adjusted to B; the mass proportion of the first acid-base regulator is adjusted to C.
[0141] Prepare the battery:
[0142] Positive electrode slurry: The mass ratio of main material lithium iron phosphate, conductive agent conductive carbon black (SP), conductive agent carbon nanotube (CNT), and binder polyvinylidene fluoride (PVDF) is 96.7:0.8:0.5:2.0;
[0143] PVDF was dissolved in N-methylpyrrolidone (NMP) at a solid content of 7% to prepare PVDF glue, and then CNT and SP were added to the PVDF glue according to the above ratio, stirred for 1 to 2 hours, and then lithium iron phosphate was added in two steps and stirred thoroughly to obtain a positive electrode slurry;
[0144] Positive electrode sheet: The positive electrode slurry is uniformly coated on the current collectors of Examples 1 to 8 and Comparative Examples 1 to 4, respectively, and the positive electrode sheet is obtained by drying, rolling and cutting;
[0145] Negative electrode slurry: the mass ratio of graphite, conductive agent SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) is 96.3:0.5:1.2:2.0;
[0146] CMC was dissolved in deionized water at a solid content of 1.2% to prepare CMC glue solution, and then SP was added to the CMC glue solution according to the above ratio, stirred for 60 minutes, and then graphite was added in two steps, stirred for 120 minutes, and finally SBR was added and stirred for 30 minutes to obtain negative electrode slurry;
[0147] Negative electrode sheet: The negative electrode slurry is evenly coated on a copper foil with a thickness of 6 μm, and the required negative electrode sheet is obtained after drying, rolling and cutting;
[0148] Electrolyte: A conventional lithium iron phosphate electrolyte was selected, the concentration of LiPF6 was 1.05-1.2 mol / L, the mixed solvent included ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC), and the mass ratio of EC, EMC and DEC was 2.5:4.0:3.5;
[0149] Diaphragm: Polypropylene (PP) coated with polymethyl methacrylate (PMMA) or PVDF on one side, or polyethylene (PE) coated with PMMA or PVDF on one side;
[0150] Assemble the battery: Assemble the prepared positive electrode sheet, negative electrode sheet, separator and electrolyte to obtain a lithium-ion battery.
[0151] Test method:
[0152] (1) pH value test of coating slurry: test with pH meter;
[0153] (2) Coating resistivity test: Tested using a four-probe resistance tester;
[0154] (3) Peel strength between coating and substrate: tested by peel force test tensile machine;
[0155] (4) Battery rate discharge test: At 25°C, charge to 3.65V at 0.5C constant current, charge to 0.05C at constant voltage, let stand for 30 minutes, then discharge to 2.0V at 0.1C, 0.33C, 0.5C, 1C, and 2C constant currents, and compare the discharge capacity ratios at different rates;
[0156] (5) Battery cycle performance test: At 25°C and 45°C, the battery was charged at a constant current of 2C to 3.65V, then charged at a constant voltage of 0.05C, left to stand for 30 minutes, and then discharged at a constant current of 1C to 2.0V. The number of cycles was 1000, and the capacity retention rate was compared.
[0157] Table 1 shows the parameter settings of Examples 1 to 8 and Comparative Examples 1 to 4
[0158]
[0159]
[0160] Table 2 shows the performance test results of the coating slurries and current collectors prepared in Examples 1 to 8 and Comparative Examples 1 to 4
[0161]
[0162]
[0163] Table 3 shows the performance test results of lithium ion batteries prepared in Examples 1 to 8 and Comparative Examples 1 to 4
[0164]
[0165] Result analysis:
[0166] From the test results of Examples 1 to 4 and Comparative Example 1, it can be seen that in Examples 1 to 4, since conductive polymers are used in the conductive agent, and based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of conductive mass carbon black a1, the mass proportion of modified conductive graphite a2 and the mass proportion of conductive polymer a3 satisfy 0.11≤a3 / (a1+a2)≤0.18, the resistivity of the coating is as low as about 2.1Ω·cm, while in Comparative Example 1, since no conductive polymer is used in the conductive agent and conventional conductive graphite is used, the resistivity of the coating is as high as 4.8Ω·cm. Therefore, by introducing conductive polymers and modified conductive graphite into the conductive agent, and based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of conductive mass carbon black a1, the mass proportion of modified conductive graphite a2 and the mass proportion of conductive polymer a3 satisfy 0.11≤a3 / (a1+a2)≤0.18, the resistivity of the coating can be reduced.
[0167] From the test results of Examples 1 to 4 and Comparative Example 2, it can be seen that in Examples 1 to 4, since the conductive agent uses conductive carbon black, modified conductive graphite and conductive polymer, and based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of conductive carbon black a1, the mass proportion of modified conductive graphite a2 and the mass proportion of conductive polymer a3 satisfy 0.11≤a3 / (a1+a2)≤0.18, the resistivity of the coating is as low as about 2.1Ω·cm, while in Comparative Example 2, since the mass proportion of conductive polymer a3 is small, a The ratio of a1 to a2 is 0.065, which does not satisfy 0.11≤a3 / (a1+a2)≤0.18, resulting in a coating resistivity as high as 4.61Ω·cm. Therefore, by introducing a conductive polymer into the conductive agent, and based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion a1 of the conductive carbon black, the mass proportion a2 of the modified conductive graphite and the mass proportion a3 of the conductive polymer satisfy 0.11≤a3 / (a1+a2)≤0.18, the coating resistivity can be reduced.
[0168] From the test results of Examples 5 to 6 and Comparative Example 3, it can be seen that in Examples 5 to 6, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the composite conductive agent is A, and the mass proportion of the modified binder is B, which satisfies: 0.81≤A / B≤1.50, so that the peel strength between the coating and the substrate is as high as 57N / m, and the resistivity of the coating is as low as about 1.7Ω·cm. In Comparative Example 3, the ratio of the mass proportion A of the composite conductive agent to the mass proportion B of the modified binder is 0.788, which does not satisfy 0.81≤A / B≤1.50, so that the peel strength between the coating and the substrate is only 44.3N / m, and the resistivity of the coating is as high as 5.26Ω·cm. Therefore, by controlling the ratio of the mass proportion A of the composite conductive agent to the mass proportion B of the modified binder to satisfy 0.81≤A / B≤1.50, the adhesion between the coating slurry and the substrate is ensured on the premise that the coating slurry has good conductive properties.
[0169] From the test results of Examples 7 to 8 and Comparative Example 4, it can be seen that in Examples 7 to 8, based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the modified binder is B, and the mass proportion of the first acid-base regulator is C, which satisfies: 0.12≤C / B≤0.32, so that the pH value of the coating slurry is increased to above 4.6, and at the same time, the peel strength between the coating and the substrate is as high as 55 N / m or more. In Comparative Example 4, due to the reduction of the mass proportion C of the first acid-base regulator, the pH value of the coating slurry is only about 4.1, and the peel strength between the coating and the substrate is only 43.2 N / m. Therefore, by controlling the mass proportion B of the modified binder and the mass proportion C of the first acid-base regulator to satisfy 0.12≤C / B≤0.32, the pH value of the coating slurry can be improved, thereby improving the peel strength between the coating and the substrate.
[0170] From the test results of Examples 1 to 8 and Comparative Examples 1 to 4, it can be seen that by taking the total mass of the composite conductive agent, the modified binder and the first acid-base regulator as the total mass, the mass proportion a1 of the conductive carbon black, the mass proportion a2 of the modified conductive graphite and the mass proportion a3 of the conductive polymer satisfy 0.11≤a3 / (a1+a2)≤0.18, the mass proportion A of the composite conductive agent and the mass proportion B of the modified binder satisfy 0.81≤A / B≤1.50, the mass proportion B of the modified binder and the mass proportion C of the first acid-base regulator satisfy 0.12≤C / B≤0.32, the discharge rate and cycle performance of the battery can be improved, wherein the 0.33C discharge rate is increased to more than 99.6%, the 0.5C discharge rate is increased to more than 97%, the 1C discharge rate is increased to more than 94%, the 2C discharge rate is increased to more than 93%, the 25°C cycle is increased to more than 90%, and the 45°C cycle is increased to more than 88%.
[0171] In summary, although the embodiments of the present application are described in detail above, the above embodiments are not intended to limit the present application, and ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A coating slurry, characterized in that: including a composite conductive agent; The composite conductive agent comprises conductive carbon black, modified conductive graphite and conductive polymer; the modified conductive graphite has unsaturated carbon-carbon double bonds and siloxane groups.
2. The coating slurry according to claim 1, characterized in that: The coating slurry also includes a modified binder and a first acid-base regulator, wherein the modified binder has an unsaturated carbon-carbon double bond; the mass ratio of the composite conductive agent to the modified binder is 42-61:40-55; the mass ratio of the modified binder to the first acid-base regulator is 40-55:3-8.
3. The coating slurry according to claim 1, characterized in that: The mass ratio of the conductive carbon black, the modified conductive graphite and the conductive polymer is 20-28:18-25:4-8; and / or, The particle size D50 of the modified conductive graphite is 3 um to 8 um; and / or, The conductive polymer is selected from PEDOT:PSS; and / or, The pH value of the coating slurry is 4 to 6; and / or, The solid content of the coating slurry is 8% to 18%.
4. A method for preparing a coating slurry, characterized in that: include: Dissolving the composite conductive agent, the modified binder, the first acid-base regulator and the wetting agent in deionized water, stirring and mixing, to obtain a coating slurry; The composite conductive agent comprises conductive carbon black, modified conductive graphite and conductive polymer; the modified conductive graphite has unsaturated carbon-carbon double bonds and siloxane groups.
5. The method for preparing the coating slurry according to claim 4, characterized in that: Based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the conductive carbon black is a1, the mass proportion of the modified conductive graphite is a2, and the mass proportion of the conductive polymer is a3, satisfying: 0.11≤a3 / (a1+a2)≤0.18; and / or, Based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the composite conductive agent is A, the mass proportion of the modified binder is B, and the following conditions are satisfied: 0.81≤A / B≤1.50; and / or, Based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the modified binder is B, the mass proportion of the first acid-base regulator is C, and the following condition is satisfied: 0.12≤C / B≤0.
32.
6. The method for preparing the coating slurry according to claim 4, characterized in that: Based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the conductive carbon black is 20% to 30%; and / or, Based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the modified conductive graphite is 18% to 25%; and / or, The conductive polymer accounts for 4% to 8% by weight based on the total weight of the composite conductive agent, the modified binder and the first acid-base regulator; and / or Based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass of the modified binder accounts for 40% to 55%; and / or, Based on the total mass of the composite conductive agent, the modified binder and the first acid-base regulator, the mass proportion of the first acid-base regulator is 3% to 8%; and / or, Based on the total mass of the deionized water, the mass proportion of the wetting agent is 1% to 2%.
7. The method for preparing a coating slurry according to claim 4, characterized in that: The preparation method of the modified conductive graphite comprises: After the conductive graphite and the first solvent are mixed, the first silane coupling agent and the polyether-modified siloxane are added, and the mixture is stirred, mixed and reacted to obtain the modified conductive graphite; The molar ratio of the conductive graphite, the first silane coupling agent and the polyether-modified siloxane is 1:0.05:0.05; The first silane coupling agent is selected from silane coupling agents containing unsaturated carbon-carbon double bonds at the ends; The first solvent is selected from at least one of toluene, dimethyl ketone and xylene.
8. The method for preparing a coating slurry according to claim 4, characterized in that: The preparation method of the modified binder comprises: Under an inert atmosphere, dissolving a crosslinking agent and a second silane coupling agent in deionized water, heating, stirring, reacting, and then adding a second acid-base regulator and keeping the temperature to obtain the modified binder; The molar ratio of the cross-linking agent, the first silane coupling agent and the second acid-base adjusting agent is 0.05:1:1; The cross-linking agent is selected from at least one of acrylic acid, acrylic ester, acrylonitrile, and acrylic acid-hydroxylactone; The second silane coupling agent is selected from silane coupling agents containing unsaturated carbon-carbon double bonds at the ends; The second acid-base regulator is selected from at least one of ammonium bicarbonate, sodium hydroxide, lithium hydroxide, and calcium hydroxide.
9. A pole piece, characterized in that: It includes a current collector, which includes a substrate and a coating located on at least one side of the substrate, and the coating is prepared using the coating slurry described in any one of claims 1 to 3, or prepared using a coating slurry prepared by the coating slurry preparation method described in any one of claims 4 to 9.
10. A battery, characterized in that: Comprising the pole piece as claimed in claim 9.
Citation Information
Patent Citations
Lithium ion battery cathode slurry and preparation method thereof
CN109037676A
Preparation method of lithium titanate negative pole piece, lithium titanate negative pole piece and lithium ion battery containing negative pole piece
CN110233243A
Graphite heat pipe for new energy and preparation method thereof
CN117613454A
Preparation method of high-strength carbon-coated aluminum foil current collector for lithium battery
CN118016897A
Composite conductive adhesive as well as preparation method and application thereof
CN118448634A
Cited By
Carbon-coated slurry and preparation method thereof, positive plate and battery
CN120399523A
